Serious Games in der Logistik: Generalisierbarkeit und Zertifizierung - Wilhelm Koop; Markus Kleffmann; Arne Gels; Thomas Neukirchen; Stefanie Jäger; Matthias Klumpp (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2018)
– This eighth and final working paper in the context of the research project MARTINA recaps the project's goals and concepts as well as organization and draws balance with respect to the implemented Solution for mobile learning in logistics (app). This is done focusing on didactics and generalizability. In addition to implementation and testing of a prototypical application, transfer potential to other industries should be explored. Thus, game principles and content of the MARTINA app were separated and the latter made accessible to users without programming knowledge via the 'App Configurator'. This process improvement has been implemented and tested with the topic office security (workplace security and fire protection measures) as part of the final version. This volume deals with the subject of generalizability in detail, discusses separation of game principles from content, app configurator and user commentary. Finally, using the considerations of the initial phase of the project, motivational game design and certification requirements are discussed. It became clear in the course of the project and in dialogue with practical partners balancing of these goals poses the main challenge for successful design of mobile learning applications.
Keywords: 650